1996
DOI: 10.1097/00004694-199607000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Severe Torsional Malalignment Syndrome

Abstract: Over a 7-year period (1984-1991), nine patients (aged 10-18 years) with 13 involved extremities were operatively treated for symptomatic severe torsional malalignment of the lower extremity and associated patellofemoral pathology. Physical examination and analysis of gait revealed severe rotational deformity characterized by excessive femoral anteversion and external tibial torsion. The cosmetic and functional pathologic effect of this torsional malalignment was centered about the knee joint. In all patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
1
26
0
9
Order By: Relevance
“…The resultant gait abnormalities and pain may occur in patients with myelodysplasia [6,8,28] with potential long-term effects of arthritis [29]. Similar findings were described in those with no neuromuscular disorder [5,14,16]. Correction of the deformity results in improvements in symptoms and the abnormal knee forces [6,14].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The resultant gait abnormalities and pain may occur in patients with myelodysplasia [6,8,28] with potential long-term effects of arthritis [29]. Similar findings were described in those with no neuromuscular disorder [5,14,16]. Correction of the deformity results in improvements in symptoms and the abnormal knee forces [6,14].…”
Section: Introductionmentioning
confidence: 81%
“…It is not possible to discern what part of the kinematic improvements were responsible for this as crouch and patella alta may have contributed to the patient's symptoms. Delgado et al [5] reported on a small series of normal children with this entity who underwent tibial osteotomies focusing on improving patella-femoral knee pain and knee joint axis rotation. The study did not employ 3D gait analysis but did report improvement in rotational profile on physical examination and all nine patients were reported to have improved functionally.…”
Section: Discussionmentioning
confidence: 99%
“…. Normalmente la combinación de anteversión femoral severa (AFE) y torsión tibial externa (TTE) se conoce como síndrome de malaalineación o desalineación torsional severa [4][5][6] . Es bien conocido que la mayor parte de los trastornos torsionales se resuelven o acomodan con la edad.…”
Section: Introductionunclassified
“…휜 다리의 치료법으로, 5cm이하일 경우 신장 운동과 5cm이상일 경우 수술적 치료를 추천하였다 (Delgado, 1996). 신장 운동은 상해의 예방과 근 긴장이나 통증 감 소, 관절가동범위 증진, 외상과 고정에 의한 기능회복 (Halbertsma과 Goeken, 1994)과 결합조직의 신장 효과 (Smith, 1994), 그리고 운동수행 능력의 강화와 근골격계 재활에 도움을 준다 (Worrell 등, 1994).…”
unclassified